Environmental DNA metabarcoding of fish communities in a small hydropower dam reservoir: a comparison between the eDNA approach and established fishing methods. Issue 1 (31st December 2022) - Li, Hai; Yang, Fang; Zhang, Ran; Liu, Shigang; Yang, Zhijin; Lin, Longshan; Ye, Sunzhong
Abstract: Environmental DNA methods have emerged as a promising tool in fish diversity studies and fishery management in various aquatic ecosystems. However, eDNA metabarcoding of fish communities in small hydropower dam reservoirs has received limited attention. In this study, we tested whether eDNA metabarcoding was an appropriate approach for the characterization of fish communities and fishery stock assessment by comparing its results with combined capture-based fishing methods and hydroacoustic surveys, which involved species detection and abundance/biomass evaluation. Our results indicated that the species detection performance of eDNA metabarcoding was basically similar to that of traditional capture-based fishing gear. However, it was also noteworthy that the eDNA method failed to cover all species detected by capture-based method, although some additional species were found. Besides, although we observed a significant correlation between site occurrence and sequence abundance for fishes, an effort to quantitatively establish a correlation between eDNA sequence counts and fish abundance/biomass was unsuccessful. Therefore, our study suggested that eDNA metabarcoding was an important supplementary tool to traditional capture-based fishing methods for the investigation and biomonitoring of fish diversity in small hydropower dam reservoirs. Further studies on the mechanisms of eDNA production, persistence, transportation and degradation in reservoirs might facilitate the interpretation of fish abundance and biomass from eDNA data.